Resonant energy transfer in Si Nanocrystal Solids - Limpens, Rens (2018)
Energy exchange between closely packed semiconductor quantum dots allows for long-range transfer of electronic energy and enables new functionalities of nanostructured materials with a huge application potential in photonics, optoelectronics, and photovoltaics. This is illustrated by impressive advances of quantum-dot solids based on nanocrystals (NCs) of direct bandgap materials, where this effect has been firmly established. Regretfully, the (resonant) energy transfer in close-packed ensembles of NCs remains elusive for silicon the main material for electronic and photovoltaic industries. This is the subject of the present study in which we conclusively demonstrate this process taking place in dense dispersions of Si NCs in an SiO2 matrix. Using samples with different NC configurations, we can directly determine the wavelength dependent energy transfer rate and show that it (i) can be modulated by material parameters, and (ii) decreases with the NCs size, and thus being consistent with the energy flow proceeding from smaller to larger NCs. This result opens the way to new applications of Si NCs, requiring energy transport and extraction. In particular, it forms a fundamental step toward development of an excitonic all-Si solar cell, operating in some analogy to polymer devices.